LITERATURE OF SOCIALIST REALISM AND THE PROTOTYPES IT CREATED IN ALBANIA - Qafleshi, Enkelena (Acta Scientiae et Intellectus, 2024)
In this paper I will attempt to analyze how the literature of Socialist Realism reflected the changes and flexibility of the Albanian society during the period of Communism. And these changes and flexibility projected in philosophy and ideology in power significantly emerge in the literature of that season of time within the frame of gender roles also under the perspective of literature of Socialist Realism. In this venue, the prototypes developed by the literature of Socialist realism and scenarios conceived, as their contextual adjustment, evidenced the changes and flexibility in gender roles dressing up the characters of both genders with equal responsibilities and loaded them with importance and significance.